Surviving ODL: Language learners' perspective / Asmahanim Mohamad Yusuf, Rodhiah Amzah and Nur Ain Yaacob - Mohamad Yusuf, Asmahanim; Amzah, Rodhiah; Yaacob, Nur Ain (2021)
The Covid-19 pandemic has altered the students' need to learn language. They are expected to be independent in learning and able to comprehend and understand the lectures given through online learning. Traditional face-to-face learning has evolved to distance learning, in which digital technology works as a medium in designing and providing better learning perspectives and learning experiences to both students and lecturers (Rapanta et al., as cited in Ana Nurdini Sharin, 2021). All classes were conducted with integrating information and communication technologies (ICT), where students interact with the lecturer and other students via electronic devices, and lecturers provide them with some guidance and assistance (Anderson, 2011).